Understnading history 2 for grade 7 - Riaz, Ismat (Karachi Oxford university press, 2023)
"Understanding History 2" by Oxford University Press is a Grade 7 textbook designed to help students explore key historical events, themes, and figures. It covers periods from ancient civilizations to modern history, emphasizing critical thinking and analytical skills. The book includes maps, timelines, and primary sources, offering a comprehensive view of historical developments and their impact on the present. Engaging activities and questions are provided to reinforce learning and encourage students to connect historical knowledge with current events.